A Framework for Leveraging IT to Improve Humanitarian Response - Sekar Widyastuti Pratiwi; Nofrisel Nofrisel; Wahyu Poncotoyo (Dinasti Publisher, 2025)
This research presents a comprehensive framework for utilizing information technology (IT) to enhance the effectiveness of humanitarian logistics management. By employing value stream mapping, we conducted a thorough analysis of the current (AS-IS) business processes involved in humanitarian response. Through this analysis, we identified significant inefficiencies and bottlenecks that hinder the timely delivery of aid. Addressing these challenges, we propose a new (TO-BE) business process model that incorporates the implementation of a warehouse management system (WMS). This innovative approach is expected to significantly reduce lead times by 25%, thereby improving the overall efficiency and effectiveness of humanitarian operations.The proposed framework outlines the key steps and considerations for integrating IT solutions into humanitarian logistics, providing a valuable guide for organizations seeking to optimize their response capabilities and save lives.